Safety and tolerability of chikungunya virus-like particle vaccine in healthy adults: a phase 1 dose-escalation trial - Chang, Lee-Jah; Dowd, Kimberly A; Mendoza, Floreliz H; Saunders, Jamie G; Sitar, Sandra; Plummer, Sarah H; Yamshchikov, Galina; Sarwar, Uzma N; Hu, Zonghui; Enama, Mary E; Bailer, Robert T; Koup, Richard A; et al. (The Lancet (British edition), 2014)
Chikungunya virus—a mosquito-borne alphavirus—is endemic in Africa and south and southeast Asia and has recently emerged in the Caribbean. No drugs or vaccines are available for treatment or prevention. We aimed to assess the safety, tolerability, and immunogenicity of a new candidate vaccine. VRC 311 was a phase 1, dose-escalation, open-label clinical trial of a virus-like particle (VLP) chikungunya virus vaccine, VRC-CHKVLP059-00-VP, in healthy adults aged 18–50 years who were enrolled at the National Institutes of Health Clinical Center (Bethesda, MD, USA). Participants were assigned to sequential dose level groups to receive vaccinations at 10 μg, 20 μg, or 40 μg on weeks 0, 4, and 20, with follow-up for 44 weeks after enrolment. The primary endpoints were safety and tolerability of the vaccine. Secondary endpoints were chikungunya virus-specific immune responses assessed by ELISA and neutralising antibody assays. This trial is registered with ClinicalTrials.gov, NCT01489358. 25 participants were enrolled from Dec 12, 2011, to March 22, 2012, into the three dosage groups: 10 μg (n=5), 20 μg (n=10), and 40 μg (n=10). The protocol was completed by all five participants at the 10 μg dose, all ten participants at the 20 μg dose, and eight of ten participants at the 40 μg dose; non-completions were for personal circumstances unrelated to adverse events. 73 vaccinations were administered. All injections were well tolerated, with no serious adverse events reported. Neutralising antibodies were detected in all dose groups after the second vaccination (geometric mean titres of the half maximum inhibitory concentration: 2688 in the 10 μg group, 1775 in the 20 μg group, and 7246 in the 40 μg group), and a significant boost occurred after the third vaccination in all dose groups (10 μg group p=0·0197, 20 μg group p<0·0001, and 40 μg group p<0·0001). 4 weeks after the third vaccination, the geometric mean titres of the half maximum inhibitory concentration were 8745 for the 10 μg group, 4525 for the 20 μg group, and 5390 for the 40 μg group. The chikungunya VLP vaccine was immunogenic, safe, and well tolerated. This study represents an important step in vaccine development to combat this rapidly emerging pathogen. Further studies should be done in a larger number of participants and in more diverse populations. Intramural Research Program of the Vaccine Research Center, National Institute of Allergy and Infectious Diseases, and National Institutes of Health.